Efficacy beliefs and motivational dynamics in early-season collegiate swimming relays - Hwang, S.; Sedabres, K.; Dithurbide, L.; Feltz, D. (International Journal of Sports Science & Coaching, 2023)
This study examined the moderating effects of efficacy beliefs and perceived indispensability on individual efforts in early-season collegiate swimming relays. Effort changes from swimmers` individual best times to relay-leg times were compared as a function of relay members` relative strength (i.e., fastest or slowest) and serial position (i.e., first or last leg). Participants (N = 199) were collegiate swimmers in 200, 400, or 800-yard freestyle relays at fall invitational meets providing 260 cases included for analysis. Individual lifetime best times, adjusted relay times, rank, serial position, and self-report measures (i.e., efficacy, perceived indispensability of their relay performance) were used for hierarchical multiple regressions. Results indicated that the slowest relay members came closer to their individual best times compared with their team members. The fastest members showed less effort change toward their individual best times than their team members. However, efficacy beliefs in one's teammates had a small positive moderating influence on the fastest members` effort in relay performances. Based on our results, we recommend Division II and III collegiate coaches not be too concerned with positional order by particular rank at early season invitationals; instead, focus on how to obtain the most effort from each relay member. However, the slowest swimmers may perform better if not positioned first.